Projekcja wielostanowa w szacowaniu wydatków systemów emerytalnych - Obidziński, Piotr (An Application of Multidimensional Household Projection Model to Estimate Future Retiring System Expenditures, 2006)
Changes in household structures may have profound consequences for several other aspects of society, like consumption, housing, labour force participation, commuting and tax revenue. The application of the household model to social security enables to perceive the link between demography and social security. The model is an effect of research project "The impact of changing household structure on future social security expenditure in the Netherlands". The article presents a dynamic household model based on the insights multidimensional demography and apply that model to trace the present and future household situation in Poland and to estimate future retiring system expenditures.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1108, s. 143-153